Program Sosialisasi Stunting Dan Monitoring Kehamilan Ibu-Ibu Di Desa Tlogo, Sukoharjo, Wonosobo - Rifqi Aulia Rahman; Dika Lita Pangestu; Elmida Cahyaningrum; Dewi Nur Lusiana; Eva Supranti; Adenia Shifi Adiba; Dyah Arumsari; Istiyanah Istiyanah; Muhammad Mauludin; Zidan Awaly Az Zaky; Ikhya Abidur Rouf (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
The problem of stunted growth is one of the nutritional problems of the Indonesian nation. Stunting is nutritional status based on the PB/U or TB/U index wherein anthropometric standards for assessing children's nutritional status, the measurement results are at the threshold. Stunting that has occurred, if not balanced with catch-up growth (growth of work) will result in decreased growth. The problem of stunting is a public health problem that is associated with an increased risk of illness, death, and barriers to growth, both motor and mental. Seeing the dangers caused by stunting, the village midwife is committed to handling and reducing the prevalence of stunting which was discussed through interviews about stunting interventions held with KPM members for the acceleration of stunting management in 2022 for 30 days in Tlogo village. That the socialization discussed the need to strengthen coordination and expand the scope of programs carried out by members of the 2022 TbR KPM and also focus on reviewing the policy of the nutrition improvement movement as evidenced in the first 1000 days of a baby's life in the Tlogo an area called Scaling Up Nutrition (SUN). It aims to improve the quality of the program in order to reduce the stunting rate in each region according to the records of the village/village midwife.